Economic activity of the Kazan City Duma in the 1870s–1880s: Considering the development of local entrepreneurship - G.V. Ibneyeva; A.G. Yakupov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article discusses the results of a complex study of the Kazan City Duma’s steps to advance local entrepreneurship during the 1870s–1880s under the conditions of the city reform initiated by Alexander II. The mechanism of issuing the following types of entrepreneurial certificates is analyzed: trade certificates, capture and estate manager’s certificates, certificates for the trade in gold and silver items, and trade powers of attorney. The quantitative data obtained from the research of clerical documents stored in the National Archives of the Republic of Tatarstan show that trade certificates and certificates for the trade in gold and silver items were granted on a stable basis. The number of trade powers of attorney issued in 1870–1876 increased substantially, which is explained by the active development of trade with various cities. In 1876–1880, the volume of all types of documents that allowed the entrepreneurial activity decreased. This trend was driven by the reduction in civil industry funding during the Russo-Turkish War of 1877–1878, as well as by the spread of conservative sentiments within the ruling elite by the end of Alexander II’s reign.